Analisis Kinerja Organisasi Dinas Koperasi dan UKM Dalam Pengembangan Koperasi (Studi pada Dinas Koperasi dan UKM Kota Malang) - Pratama, Brian (Jurnal Administrasi Publik, 2013)
Abstract: The condition of the cooperative is generally still weak, good condition of capital, management and organization, technology and networking efforts, and the control of the market. Department of Cooperatives and SMEs is implementing elements of the local authorities have an important role in developing the activities of cooperatives and SMEs. Therefore, the more will be explained how organizational performance service of cooperatives and SMEs within to developt cooperative activities. This research arranged into two focus research. First, to describe and analyze the performance of the organization Department of Cooperatives and SMEs of Malang City to developt cooperatives through six indicators measuring the performance of the Organization, namely: indicators of inputs, processes, outputs, outcomes, benefits, impacts. Second, it aims to to describe and analyse the factors affecting the iplementation of services work programs for to developt cooperative. Results of the research found that there were seven service work programs, but still less satisfying service quality. This is due to the limitations of the number of employees, on-site service is still inadequate, the prerequisites and procedures for the management of the cooperative is still too complicated, which affects the less maximum organizational performance of Department of Cooperatives and SMEs.Â Abstrak: Kondisi koperasi umumnya masih lemah, baik kondisi permodalan, manajemen dan organisasi, teknologi dan jaringan usaha, dan penguasaan pasar. Dinas Koperasi dan UKM merupakan unsur pelaksana Pemerintah Daerah mempunyai peran penting dalam mengembangkan kegiatan Koperasi dan UKM. Maka dari itu, lebih lanjut akan dijelaskan bagaimana kinerja organisasi Dinas Koperasi dan UKM dalam menumbuhkembangkan kegiatan koperasi. Penelitian ini disusun kedalam dua fokus penelitian. Pertama, mendiskripsikan dan menganalisis kinerja organisasi Dinas Koperasi dan UKM Kota Malang dalam pengembangan koperasi melalui enam indikator pengukuran kinerja organisasi, yakni: indikator masukan, proses, keluaran, hasil, manfaat, dampak. Kedua, bertujuan untuk mendiskripsikan dan menganalisis faktor-faktor yang mempengaruhi dalam pelaksanaan layanan program kerja untuk pengembangan koperasi tersebut. Hasil penelitian ditemukan bahwa terdapat tujuh layanan program kerja dinas, namun kualitas layanan masih kurang memuaskan. Hal ini dikarenakan keterbatasan jumlah pegawai, fasilitas dinas masih kurang memadai, prasyarat dan prosedur kepengurusan koperasi masih terlalu ribet, yang berdampak pada kurang maksimalnya kinerja organisasi Dinas Koperasi dan UKM.